Factors That Encourage Consumers to Choose Dexlite as Fuel for Diesel Vehicles - Kushariyadi Kushariyadi (Fakultas Ekonomi Universitas Garut, 2025)
Dexlite is a diesel fuel product that was just released in mid-2016. This study aims to explain the influence of product quality, promotion, and price of Dexlite on purchasing decisions so that it can be used as a reference for developing Dexlite marketing strategies in Malang City. The type of research used is explanatory with a quantitative approach. The variables in this study include product quality, promotion, and price. The population of this study is Dexlite consumers in the private vehicle user sector in Malang City. The sample used in this study was 100 respondents taken using convenience sampling and data collection methods using questionnaires. The results of this study include: 1. The product quality variable has a positive and significant effect on Dexlite purchasing decisions in Malang City. 2. The promotion variable has a positive and significant effect on Dexlite purchasing decisions in Malang City. 3. The price variable has a positive and significant effect on Dexlite purchasing decisions in Malang City. 4. The product quality, promotion, and price variables together have a positive and significant effect on T purchasing decisions.